1996
DOI: 10.1002/(sici)1097-0320(19960701)24:3<277::aid-cyto11>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear texture analysis: A new prognostic tool in metastatic prostate cancer

Abstract: This report describes the prognostic value of computerized nuclear texture analysis in metastatic prostate cancer. Seventy‐seven patients with histologically verified prostate carcinomas and skeletal metastases were selected from a Scandinavian multicenter study (SPCG‐2). Thirty‐six therapy‐resistant patients experienced objective progression and cancer‐related death within 2 years after orchiectomy. Thirty patients responded well to orchiectomy, i.e., showed objective disease remission and no signs of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Greater amounts of proteins and nucleic acids, with improved integrity, can be extracted from ultrasound-fixed tissues than from conventionally fixed tissues to support general molecular analysis (Figures 8 and 9). Previous reports have shown that morphological nuclear grading on radical prostatectomy specimens 25,26 and the specificity and intensity of ER staining on breast tissues [27][28][29] are sensitive to formalin fixation time. Our results (Figures 3 and 4) clearly show that 5-min ultrasound-facilitated formalin fixation achieved the same degree of formalin fixation as conventional methods lasting 16 h or more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater amounts of proteins and nucleic acids, with improved integrity, can be extracted from ultrasound-fixed tissues than from conventionally fixed tissues to support general molecular analysis (Figures 8 and 9). Previous reports have shown that morphological nuclear grading on radical prostatectomy specimens 25,26 and the specificity and intensity of ER staining on breast tissues [27][28][29] are sensitive to formalin fixation time. Our results (Figures 3 and 4) clearly show that 5-min ultrasound-facilitated formalin fixation achieved the same degree of formalin fixation as conventional methods lasting 16 h or more.…”
Section: Discussionmentioning
confidence: 99%
“…As reported previously, shorter fixation caused nuclear artificial changes that simulate a lower nuclear grading. 25,26 Except in one case where 10% of the prostatectomy showed a nuclear appearance of higher grade, grading of ultrasound-fixed tissue was the same as that determined from conventional formalin-fixed and paraffinembedded tissue. This study indicates that nuclear appearance is almost identical following 5-min ultrasound fixation or 72-h conventional formalin fixation.…”
Section: Nuclear Morphology In Tissues Preserved By Conventional and mentioning
confidence: 99%
“…Subsequently, several investigators (23-28) have used nuclear alterations to predict pathologic stage and prognosis for PCa patients. Nuclear morphometric alterations measured by computer-assisted image analysis can detect abnormal DNA content representing large scale chromosomal alterations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The customary mathematical/statistical analytic models either do not allow its use or simply are not suitable to use it. In karyometry most image analytic software packages routinely compute the values of about one hundred different variables [1][2][3][4][5][6][7]. Yet, only a few -typically less than eight -are used in a discriminant function.…”
Section: Diagnostic Information Extraction (Karyometry)mentioning
confidence: 99%